2022
DOI: 10.1038/s41467-021-27758-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota promotes cholesterol gallstone formation by modulating bile acid composition and biliary cholesterol secretion

Abstract: Cholesterol gallstone disease is a worldwide common disease. Cholesterol supersaturation in gallbladder bile is the prerequisite for its pathogenesis, while the mechanism is not completely understood. In this study, we find enrichment of gut microbiota (especially Desulfovibrionales) in patients with gallstone disease. Fecal transplantation of gut microbiota from gallstone patients to gallstone-resistant strain of mice can induce gallstone formation. Carrying Desulfovibrionales is associated with enhanced ceca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…Further community heatmap analysis on genus level revealed that LCA/LGG‐LDB treatment significantly increased the relative abundance of Lactobacillus , Colidextribacter , Allobaculum of Firmicutes, and Enterorhabdus , Bifidobacterium , Gordonibacter of Actinobacteria, and significantly decreased the relative abundance of Muribaculum of Bacteroidetes in comparison to ANIT group (Figure 4E,F ). Besides, the relative abundance of Desulfovibrio (Desulfobacterota), which is proved to active hepatic FXR and inhibit CYP7A1 expression, [ 30 ] was also significantly elevated in LCA/LGG‐LDB treatment. The gut microbiota analysis proved that LCA/LGG‐LDB can effectively correct disordered gut microbiota caused by ANIT.…”
Section: Resultsmentioning
confidence: 99%
“…Further community heatmap analysis on genus level revealed that LCA/LGG‐LDB treatment significantly increased the relative abundance of Lactobacillus , Colidextribacter , Allobaculum of Firmicutes, and Enterorhabdus , Bifidobacterium , Gordonibacter of Actinobacteria, and significantly decreased the relative abundance of Muribaculum of Bacteroidetes in comparison to ANIT group (Figure 4E,F ). Besides, the relative abundance of Desulfovibrio (Desulfobacterota), which is proved to active hepatic FXR and inhibit CYP7A1 expression, [ 30 ] was also significantly elevated in LCA/LGG‐LDB treatment. The gut microbiota analysis proved that LCA/LGG‐LDB can effectively correct disordered gut microbiota caused by ANIT.…”
Section: Resultsmentioning
confidence: 99%
“…All this makes the perfect environment for D . desulfuricans to thrive, producing H 2 S that not only can be toxic for the epithelial barrier [ 47 ] but can also modulate the hepatic bile acid metabolism by induction of the farnesoid X receptor (FXR) and inhibition of cholesterol 7 alpha-hydroxylase (CYP7A1), to produce more hydrophobic bile acids due to increased deoxycholic acid (DCA) and decreased β-muricholic acid (βMCA), eventually giving place to hepatic and biliary cholesterol overloading and even promoting gallstone formation [ 48 ]. Finally, Desulfovibrio desulfuricans was the first species where a system to produce trimethylamine (TMA) was detected and where TMA production was proven [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as it has been mentioned above, in the BT diet there is also a number of exogenous sulfate-conjugated metabolites already available in the butter [35,36] and, in the host, part of the high amount of bile acids produced are 3α-sulfated or 3β-sulfated bile acids where the sulfate can be removed by many intestinal bacterial species [46]. All this makes the perfect environment for D. desulfuricans to thrive, producing H 2 S that not only can be toxic for the epithelial barrier [47] but can also modulate the hepatic bile acid metabolism by induction of the farnesoid X receptor (FXR) and inhibition of cholesterol 7 alpha-hydroxylase (CYP7A1), to produce more hydrophobic bile acids due to increased deoxycholic acid (DCA) and decreased β-muricholic acid (βMCA), eventually giving place to hepatic and biliary cholesterol overloading and even promoting gallstone formation [48]. Finally, Desulfovibrio desulfuricans was the first species where a system to produce trimethylamine (TMA) was detected and where TMA production was proven [49].…”
Section: Plos Onementioning
confidence: 99%
“… 35 A recent study demonstrated that Desulfovibrionale also has 7α-HSDH activity, and mice carrying Desulfovibrionale produce more secondary BAs. 36 …”
Section: The Interaction Between Gut Microbiota and Secondary Basmentioning
confidence: 99%